Halal Certification in Used Goods Products in the Perspective of Islamic Law - Suhri Hanafi; Muhammad Syarif Nurdin (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam)
This study aimed to assess the halal certification of utilized goods from the perspective of Islamic law. It is qualitative field research. The purposive sampling technique was used to gather two informants for this study. The primary data used in this study were from the results of interviews with research subjects. Meanwhile, the secondary data were secondary sources of books, journals on halal products, and other books relevant to the study issue. In-depth interviews and tracking documentations were employed to gather the data. Data analysis involved data condensation, data presentation, and conclusion drawing. Based on the field study results, halal certification on utilized goods is intended to provide benefits by emphasizing precautionary principles. Furthermore, numerous phases of time are applied to utilized goods before they are required to be labeled halal. They have to follow the halal procedures referred to the LPPOM MUI halal assurance system to receive a halal certificate. According to a review of Islamic law, halal certification on utilized goods follows the principles of Islamic law stipulation, which is to provide benefits. The benefits are generated at the hajiyat (secondary) level. Furthermore, the Islamic law's conformity to halal certification of utilized goods is indicated in the fulfillment of basic principles of Islamic law. They are the principles of justice, legal certainty, practicality, monotheism, freedom, and gradual law stipulation.